2011
DOI: 10.1186/1752-1947-5-45
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after en bloc resection and reconstruction of a solitary paraganglioma metastasis in the first lumbar vertebral body: a case report

Abstract: IntroductionParagangliomas are rare tumors that originate from the autonomic nervous system-associated paraganglia. They metastasize infrequently. Malignancy can only be demonstrated by the presence of chromaffin tissue at sites where it usually is not present, such as bone, lung or liver, or local recurrence after total resection of a primary mass. Paragangliomas within the central nervous system are usually intradural near the conus medullaris. The metastatic spread of a retroperitoneal paraganglioma to a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…Mertens demonstrated the successful regression and palliation of metastases of paraganglioma with chemotherapy, particularly with combined cyclophosphamide, vincristine and dacarbazine (13). However, there were also a number of disappointing reports on chemotherapy for this type of tumor (8,11,12,15). In our study, 6 patients with primary paraganglioma only underwent surgery and the follow-up showed good outcomes and no recurrence.…”
mentioning
confidence: 78%
“…Mertens demonstrated the successful regression and palliation of metastases of paraganglioma with chemotherapy, particularly with combined cyclophosphamide, vincristine and dacarbazine (13). However, there were also a number of disappointing reports on chemotherapy for this type of tumor (8,11,12,15). In our study, 6 patients with primary paraganglioma only underwent surgery and the follow-up showed good outcomes and no recurrence.…”
mentioning
confidence: 78%
“…The strategy must be carried on the adequate study of the tumors according to the Tokuhashi and Tomita scoring system. Alexander Richter et al [6] had reported TES and reconstruction of a solitary spinal MPG in L1 vertebral body with a follow-up time for 10 years which indicated the significance of TES. As a result, with surgical and internal fixation techniques rapidly improving, total resection, even TES when possible, is necessary to treat spinal MPG, especially solitary lesion, to achieve satisfying results.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy with a total of 30-50 Gy had been reported to be helpful for the treatment of spinal MPG [2,6,12,15,30]. Mertens et al [28] had reported initial chemotherapy including cyclophosphamide, vincristine and dacarbazine could alleviate symptoms at metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations